Understanding the development of peace concept in Children’s drawings - Ali Mohammad Rezaei, Reza Samadi; Amin Beydokhti, Ali Akbar; Farahnaz KianErsi, Mahmood Najafi (Opción, 2019)
This study aimed at finding thinking content of 63 boys at the age of 6-13 who are studying in schools located in districts 3 and 4 of Tehran in terms of the peace concept in drawing using qualitative research methodology of phenomenography. Findings implied that the peace concept included developed and social dimensions in each age group indicating the transformational process of this concept in children. In conclusion, it is essential to pay attention to developmental capacities of peace concept in order to have children with practical and real skills in relation with the peaceful life for a healthy future.